Late Presentation of Persistent Left Superior Caval Vein in a Univentricular Heart with Successful Transcutaneous Occlusion Using Cera Lifetech Atrial Septal Occluder - Iyad AL-Ammouri; Ahmad Alhourani; Ayoub Innabi (Case Reports in Cardiology)
We present a case of persistent left superior caval vein in a univentricular heart presenting with progressive and disabling cyanosis in a 35-year-old man eighteen years after his Kawashima operation. The vein was successfully occluded using an atrial septal occluder with significant improvement of symptoms and oxygen saturation.